2022
DOI: 10.1002/hyp.14613
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal dispersion affected by willow patches of low areal coverage

Abstract: Vegetation notably influences transport and mixing processes and can thus be used for controlling the fate of substances in the hydro-environment. Whilst most work covers fully vegetated conditions, the novelty of this paper is to focus on flows with real-scale flexible willow patches. We aimed to investigate how longitudinal dispersion varies according to the spatial distribution, density and coverage of the patches and to evaluate the explanatory power of predictors that consider the hydraulics, vegetation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…However, the study of Vastila [41] showed that p I had noticeably poorer predictive power than that observed in the sparse vegetated patches condition of Park and Hwang [43] , with 1-3 orders magnitude lower value. The results indicated that both patch density and location control dispersion.…”
Section: Influences Of Vegetation Patchesmentioning
confidence: 74%
See 4 more Smart Citations
“…However, the study of Vastila [41] showed that p I had noticeably poorer predictive power than that observed in the sparse vegetated patches condition of Park and Hwang [43] , with 1-3 orders magnitude lower value. The results indicated that both patch density and location control dispersion.…”
Section: Influences Of Vegetation Patchesmentioning
confidence: 74%
“…When vegetated patches grow in channels, they create stem-scale vortexes and patch-scale vortexes that impact dispersion [92] . The highest dispersive fractions of vegetated patches are typically larger than those of randomly distribution stems [41,93] . Two problems have drawn the attention of researchers.…”
Section: Influences Of Vegetation Patchesmentioning
confidence: 97%
See 3 more Smart Citations